The Semantic Role of Classifiers in Japanese - Yasutada Sudo (Baltic International Yearbook of Cognition, Logic and Communication, 2016)
In obligatory classifier languages like Japanese, numerals cannot directly modify nouns without the help of a classifier. It is standardly considered that this is because nouns in obligatory classifier languages have ‘uncountable denotations’, unlike in non-classifier languages like English, and the function of classifiers is to turn such uncountable denotations into something countable (Chierchia 1998a,b, Krifka 2008, among many others). Contrary to this view, it is argued that what makes Japanese an obligatory classifier language is not the semantics of nouns but the semantics of numerals. Specifically, evidence is presented that numerals in Japanese cannot function as predicates on their own, which is taken as evidence that the extensions of numerals in Japanese are exclusively singular terms. It is then proposed that the semantic function of classifiers is to turn such singular terms into modifiers/predicates. It is furthermore claimed that the singular terms denoted by numerals are abstract entities (cf. Rothstein 2013, Scontras 2014a,b), and proposed that the reason why they cannot have modifier/predicate uses in obligatory classifier languages like Japanese is because the presence of classifiers in the lexicon blocks the use of a type-shifting operator that turns singular terms denoted by numerals into predicates (cf. Chierchia 1998a,b).
Keywords: classifier; numeral; semantic parameter; Japanese